2019
DOI: 10.1007/s10681-019-2449-7
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to insect pests in wheat—rye and Aegilops speltoides Tausch translocation and substitution lines

Abstract: Various insect pests attack wheat (Triticum aestivum L.) that can cause significant grain yield losses to the crop. Farmers usually depend on pesticides, however, smallholder farmers often have limited and ill-timed access to control methods, including insecticides. Host plant resistance is an alternative to protect grain yield and reduce costs to farmers. Three of the most serious pests of wheat are Diuraphis noxia (Kurdjumov), Mayetiola destructor (Say), and Cephus pygmeaus L. These pests occur in most of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Previously, Dn7 , Gb2 , and Gb6 resistance genes to cereal aphids have been reported on chromosome arm 1R ( Friebe et al., 1996 ; Friebe et al., 1999 ; Anderson et al., 2003 ). Also, 1RSam.1AL and MA1S.1RLe(1B), 1Re(1D) wheat–rye translocation, and substitution lines were shown with a high level of resistance against HF and RWA, and these lines are now used in the international wheat breeding programs ( Crespo-Herrera et al., 2019 ). The wheat-alien introgression lines with the presence of 1R, 1RS, 2R, 3R, 3RS, 4R, 5R, 6RL, and L. racemosus and L. mollis chromosomes provides resistance to the Syrian HF biotype.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Dn7 , Gb2 , and Gb6 resistance genes to cereal aphids have been reported on chromosome arm 1R ( Friebe et al., 1996 ; Friebe et al., 1999 ; Anderson et al., 2003 ). Also, 1RSam.1AL and MA1S.1RLe(1B), 1Re(1D) wheat–rye translocation, and substitution lines were shown with a high level of resistance against HF and RWA, and these lines are now used in the international wheat breeding programs ( Crespo-Herrera et al., 2019 ). The wheat-alien introgression lines with the presence of 1R, 1RS, 2R, 3R, 3RS, 4R, 5R, 6RL, and L. racemosus and L. mollis chromosomes provides resistance to the Syrian HF biotype.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports (Deutsch et al, 2018) have shown that an increased temperature will significantly increase the grain loss in many parts of the world in wheat, maize, and rice. Likewise, another impact of climate change would be an increased number of generations per season of multivoltine species and their accelerated development causing potentially more damage to crops (Crespo-Herrera et al, 2019). Therefore, climate change will likely threaten sustainable wheat production in the future (Crespo-Herrera et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, another impact of climate change would be an increased number of generations per season of multivoltine species and their accelerated development causing potentially more damage to crops (Crespo-Herrera et al, 2019). Therefore, climate change will likely threaten sustainable wheat production in the future (Crespo-Herrera et al, 2019). In addition, wheat production has been threatened by unexpected abiotic and biotic stresses due to abrupt environmental changes or the movement of pathogens (Bakala et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The International Center for Agricultural Research in the Dry Areas (ICARDA) in collaboration with its partners identified sources of resistance and developed germplasm carrying resistance to several of the key pests of wheat over the last 20 years, including Hessian fly and Sunn pest (Nsarellah et al, 2003); El Bouhssini et al., 2012; Emebiri et al., 2016; Bassi et al., 2019). Apart from the recently discovered sources combining resistance to Hessian fly and three aphid species (Crespo‐Herrera et l., 2019), all the resistant germplasm reported by ICARDA and its partners are for single insects ( al., 2013).…”
Section: Introductionmentioning
confidence: 99%